2014
DOI: 10.1139/cjm-2014-0485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glycerol-3-phosphate dehydrogenase on virulence factor production byPseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa establishes life-long chronic infections in the cystic fibrosis (CF) lung by utilizing various adaptation strategies. Some of these strategies include altering metabolic pathways to utilize readily available nutrients present in the host environment. The airway sputum contains various host-derived nutrients that can be utilized by P. aeruginosa, including phosphatidylcholine, a major component of lung surfactant. Pseudomonas aeruginosa can degrade phosphatidylcholine to glycerol and fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Although increased expression of the phospholipase genes was not observed under LS conditions, genes involved in glycerol uptake ( glpF ) and metabolism ( glpK , glpD ) were upregulated ≥1.50-fold under LS conditions. Recently, it was shown that CF-adapted P. aeruginosa isolates utilize glycerol as a carbon source more efficiently than nonadapted isolates ( 57 ). In addition, mutation of the glpD gene (encoding a glycerol-3-phosphate dehydrogenase) resulted in lower levels of alginate production, indicating that the glycerol catabolic pathway is indispensable for full virulence of P. aeruginosa in chronic CF infection ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although increased expression of the phospholipase genes was not observed under LS conditions, genes involved in glycerol uptake ( glpF ) and metabolism ( glpK , glpD ) were upregulated ≥1.50-fold under LS conditions. Recently, it was shown that CF-adapted P. aeruginosa isolates utilize glycerol as a carbon source more efficiently than nonadapted isolates ( 57 ). In addition, mutation of the glpD gene (encoding a glycerol-3-phosphate dehydrogenase) resulted in lower levels of alginate production, indicating that the glycerol catabolic pathway is indispensable for full virulence of P. aeruginosa in chronic CF infection ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, genes that encode the 'acetate switch', permitting a transition from rapid growth to a slower, acetatescavenging lifestyle [52], as well as dehydrogenases, hydratases and anaerobic reductases were identi ed only in LAP. Anaerobic glycerol phosphate-3-hydrogenase genes, which play a critical role in utilizing alternate nutritional sources [53] were consistently higher in LAP when compared to the other two. Genes encoding c-type cytochrome and molybdenum cofactor biosynthesis, iron-sulfur clusters, and formate dehydrogenase were also overrepresented in this cohort.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that the P. aeruginosa CF isolate, FRD1, displays a growth advantage when grown on glycerol compared to the wound isolate, PAO1 (Daniels et al 2014). Moreover, we demonstrated that glycerol-3-phosphate dehydrogenase, (glpD), is required for the optimal production of key P. aeruginosa virulence factors, including alginate production by FRD1, suggesting that glycerol metabolism may be an important factor that mediates persistence by some chronic isolates of P. aeruginosa.…”
Section: Growth On Glycerol and Deregulation Of Glycerol Metabolism Pmentioning
confidence: 88%
“…Our laboratory previously reported that the chronic CF isolate, FRD1, has a growth advantage on glycerol compared to the acute isolate, PAO1. In addition, we demonstrated that glycerol-3-phosphate (glpD) is required for the production of some P. aeruginosa virulence factors, including alginate (Daniels et al 2014), which has been shown to play an important role in biofilm architecture and protection from antimicrobials (Hentzer et al 2001). Not surprisingly, 80% of chronic infections are associated with microbial biofilm formation (Costerton et al 1999).…”
Section: R a F Tmentioning
confidence: 99%